Identity Portrayal of Dalit Characters, Class and Culture: Comparative Study on Novels Written by Dalit and Non-Dalit Novelists - Magarati, Shyam Lal; Rai, Prakash (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
The paper attempts to explore the identity portrayals of Dalit characters, their class, and culture in the Nepali texts by both Dalit and Non-Dalit writers. KoAchut? (Who is Untouchable?) by MuktinathTimsena and NayāGhar (New Home) by Bishowbhakta Dulal, are selected two novels to examine the issue of Dalit characters, class, and culture. The study employs a qualitative method, particularly textual analysis for the interpretation. The data have been meticulously extracted from the novels to compare and contrast the internal dispositions and external socio-cultural interactions of the characters represented by the writers from both mainstream community and marginalized ones in Nepali surrounding. Major drawing from Stuart Hall's opinion of discursive identity and representation in cultural studies, the study tries to include the supportive perspectives from scholars such as Chris Barker, Eagleton, and Foucault, as well as insights from Indian writers like Vandana Bhatta, Ghanshyam, and Neha Arora to augment the textual analysis. The findings emphasize a recurring theme of class struggle in both narratives, showcasing Dalit characters wrestling with poverty and disenfranchisement while non-Dalit counterparts are positioned as prosperous and influential figures. A notable discrepancy emerges as Dalit characters are relegated to minor roles, contrasting with the predominant roles given to non-Dalit characters. Interestingly, Dalit writer draws from personal experiences and real-life events while non-Dalit writer only speculates on the complex development and dogmatic progression of Dalit characters. This research sheds light on the socio-cultural complexity within Dalit literature, emphasizing the implication of comparative scrutiny in addressing the societal subtleties surrounding culture, privilege, and representation.